PENERAPAN METODE REPEATED INTERACTIVE READ ALOUD DALAM MENINGKATKAN KEMAMPUAN BAHASA RESEPTIF DAN EKSPRESIF PADA ANAK USIA DINI DI RA AR-RUM BATAM - Syahrial , Eri Syahrial; Yuniati, Devi Yuniati (Hamka Ilmu Pendidikan Islam, 2025)
Receptive and expressive language skills are important aspects in early childhood development that serve as the foundation for early communication and literacy skills. However, in learning practices in early childhood education institutions, children are still found to be less able to understand spoken language and express ideas verbally. This study aims to describe the use of the Repeated Interactive Read Aloud method in improving receptive and expressive language skills in early childhood. This study uses a qualitative approach with a descriptive research type. The research subjects were group B children at one of the early childhood islamic education institutions, RA AR-RUM Batam. Data collection techniques were carried out through observation and interviews. Data analysis techniques used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the application of the Repeated Interactive Read Aloud method can improve children's receptive and expressive language skills, such as understanding new vocabulary and story content, the ability to ask questions, answer questions, and retell the story content. This method creates an interactive, fun learning atmosphere and encourages active participation of children.